PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA ASN DENGAN KOMPENSASI SEBAGAI VARIABEL MODERATING PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KABUPATEN SITUBONDO - Mannan, Abdul; Ediyanto, Ediyanto; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this study was to analyze the influence of motivation and work discipline on asn performance with compensation as a moderating variable at the human resources development and personnel agency of situbondo regency. The population in this study involved 37 asn of the human resources development and personnel agency of situbondo regency without the leadership. Sampling in this study was carried out using a saturated sampling technique, which means that all members of the population were included as samples.The partial-least square (pls) structural equation model was used to analyze data and test hypotheses. The results of the direct effect hypothesis test using the smart pls 3.0 application showed that motivation had a significant positive effect on performance, work discipline had a significant positive effect on performance, compensation did not moderate the effect of motivation on performance, compensation did not moderate the effect of work discipline on performance.,